Pengaruh Pengungkapan Tanggung Jawab Sosial Pada Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Pemoderasi - Mutya Armika, Anak Agung Ayu; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p04, 2018)
Company value is very fundamental factor and need to be known by the investors before deciding to invest. Information disclosed by the company is a signal for investors to instill shares in the company. Information provided by companies in the form of corporate value, disclosure of social responsibility and profitability. The purpose of this study is to obtain empirical evidence of the role of profitability in moderating the influence of corporate social responsibility disclosure on firm value in basic and chemical industry companies listed on the IDX during the year 2013-2015. The population of this study amounted to 60 companies, with samples used by 57 companies using nonprobability sampling method. The dependent variable is firm value as measured by Price Book Value (PBV). The independent variable is disclosure of social responsibility as measured by the corporate social responsibility disclosure index (CSRD index) . The moderation variable is profitability measured by Return on Equity (ROE) . Data collection method used is non participant observation. The analysis technique used is Moderated Regression Analysis (MRA) . The results of the study shows the disclosure of corporate social responsibility positively affects on firm value. Profitability does not able to moderate influence of corporate social responsibility disclosure on firm value. Keywords: disclosure of corporate social responsibility, corporate value, profitability